A study on correlation between pelvic rotation and running performance for designing a running quality index - Okuno, K.; Masumoto, G.; Tezuka, K.; Noda, S.; Himeno, R. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Today, there are many people who enjoy jogging in a regular basis. Many of them uses wearable devices to log their running time, route, etc. To improve running performance, it is important to assess running qualitatively as well. However, these devices do not assess quality of running, and do not teach users what to change and how to change in order to improve quality of running. The purpose of this study is to present correlation between pelvic rotation and running performance, experimentally, and discuss how indices can be designed to assess quality of running. For the experiment, 60 student athletes participated and run 1500 meter for two times with an accelerometer and gyro meter sensor attached to their lower back. The result shows that there is a correlation between pelvic rotation and running performance. Followed by discussion for designing the indices of running quality.